1995
DOI: 10.1007/bf00294748
|View full text |Cite
|
Sign up to set email alerts
|

Early recurrence of hyperthyroidism in patients with Graves' disease treated by subtotal thyroidectomy

Abstract: Prerequisites for surgical treatment of Graves' disease are that it can be done safely and that it is associated with a low incidence of recurrent hyperthyroidism. Early recurrence is especially undesirable. We studied 728 patients with Graves' disease treated by subtotal thyroidectomy using multivariate analysis in order to determine the factors related to early recurrence. The following factors were analyzed: age, sex, duration of medical treatment, weight of resected thyroid tissue, thyroid remnant size, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…We think the ideal goal is not euthyroidism with thyroxin replacement therapy, but long-term euthyroidism without medication. Factors related to postoperative thyroid dysfunction, especially recurrent hyperthyroidism, had to be elucidated to achieve this goal and we have published several reports and concluded that thyroid remnant size is the only powerful factor related to postoperative thyroid dysfunction [4,15]. Risk factor analyses showed that female patients with high preoperative TBII level had recurrent overt hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…We think the ideal goal is not euthyroidism with thyroxin replacement therapy, but long-term euthyroidism without medication. Factors related to postoperative thyroid dysfunction, especially recurrent hyperthyroidism, had to be elucidated to achieve this goal and we have published several reports and concluded that thyroid remnant size is the only powerful factor related to postoperative thyroid dysfunction [4,15]. Risk factor analyses showed that female patients with high preoperative TBII level had recurrent overt hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal thyroid cells, especially TSCs and thyroblasts, are not likely to exist abundantly in the thyroid in adults, since the adult thyroid does not usually regenerate after partial thyroidectomy [22]. No induction of thyroid carcinomas by radiation in adults supports this assumption [11].…”
Section: Reverse Approachmentioning
confidence: 98%
“…However, in our previous study, 18 % of the Graves' disease patients treated by subtotal thyroidectomy developed recurrent hyperthyroidism after 8 years postoperatively [16] and that was an unacceptably high rate. Factors related to postoperative thyroid dysfunction, especially recurrent hyperthyroidism, had to be elucidated to achieve the ideal goal, and we have published several reports [2,3] and concluded that thyroid remnant size is the only powerful factor associated with postoperative thyroid dysfunction. Although thyroid remnant size is a significant factor related to postoperative thyroid dysfunction, patients with almost the same size thyroid remnant do not always have the same postoperative clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, preoperative TSH receptor antibody levels have a significant effect on the short-term results of subtotal thyroidectomy for Graves' disease but not on the long-term results. Long-term surgical outcomes could not be predicted on the basis of the preoperative TSH receptor antibody level [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation